Direct gravimetric determination of aerosol mass concentration in Central Antarctica. - ANNIBALDI, ANNA; TRUZZI, Cristina; ILLUMINATI, Silvia; SCARPONI, Giuseppe (Analytical Chemistry, 2011)
Accettato 25/10/2010; On line 08/12/2010